Aerobic rice cultivation for enhanced water use efficiency - S, Vijaya Kumar; Jinger, Dinesh; P, Parthiban; S, Lokesh (Indian Farming, 2018)
Overall aerobic rice technology is a promising technology that can stir up another green revolution by increasing productivity of rice using less water and direct sowing and therefore requiring less seeds, less labour, less greenhouse gases (methane) and efficient fertilizer utilization. Comparison of agronomic performance of aerobic and flooded rice in tropical areas confirmed a yield gap between aerobic and flooded rice. The possible causes for declining yield of continuous aerobic rice are: improper crop stand due to higher seedling mortality, heavy weed infestation, nutrient deficiencies (P, Fe), rootknot nematode infestation and unfavourable soil environment for semi-aquatic plants. The concept of aerobic rice holds promise for farmers in water-short irrigated rice environments where water availability at the farm level is too low or where water is too expensive to grow flooded lowland rice. Selection of good aerobic rice variety with desired physiological attributes along with good cultural practices, nutrient management practice, weed control measure, crop rotation, and brown manuring would give better performance.